2005
DOI: 10.1097/01.icu.0000172827.31985.3a
|View full text |Cite
|
Sign up to set email alerts
|

Amniotic membrane use in ophthalmology

Abstract: Amniotic membrane use in ophthalmic surgery has been shown to provide an alternative for corneal and conjunctival reconstruction in many clinically challenging situations; however, there is still a lack of scientific evidence based on randomized comparative studies to prove that its use is better than other alternative therapies for ocular surface reconstruction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
118
0
8

Year Published

2008
2008
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 177 publications
(128 citation statements)
references
References 50 publications
2
118
0
8
Order By: Relevance
“…2 Ma et al 25 have found that single-layered amniotic membrane was able to reduce the recurrence to 12.5%, which was comparable with our study. They stated that the addition of mitomycin C did not further reduce the recurrence rate.…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…2 Ma et al 25 have found that single-layered amniotic membrane was able to reduce the recurrence to 12.5%, which was comparable with our study. They stated that the addition of mitomycin C did not further reduce the recurrence rate.…”
Section: Discussionsupporting
confidence: 82%
“…2 Commonly, 8-0 vicryl or 10-0 nylon sutures are used to fixate the amniotic membrane to the episcleral tissues and surrounding conjunctiva.…”
Section: Introductionmentioning
confidence: 99%
“…The amniotic membrane has been already applied in medicine to treat burning lesions and in surgical wounds to cover tissue. Additionally, it has been used as a dressing or substrate for epithelial growth to manage several conditions of the ocular surface [5][6][7] . The amniotic membrane, or amnion, is the most interior layer of the fetus membranes.…”
Section: Introductionmentioning
confidence: 99%
“…10,12,13 The main reasons for using amniotic membrane transplantation on conjunctival defects are the positive effects on reepithelialization and inhibition of postoperative inflammation, neovascularisation, and fibrosis. 17 Pirouzian et al 11 reported that the purpose of amniotic membrane transplantation was primarily to achieve a volumetric filling of the stromal and epithelial defect after the removal of a limbal dermoid. They also Eye anticipated reduced scarring due to faster reepithelialization.…”
Section: Discussionmentioning
confidence: 99%